SISTEM INFORMASI DATA PEGAWAI PADA PUSKESMAS REMU KOTA SORONG BERBASIS WEB - Juneth Nelfia Wattimena; N Ginuny (LPPM Poltek ST Paul, 2021)
Remu Public Health Center is one of the oldest public health center in Sorong City and the only public health center with a major accreditation ranking for Papua and West Papua regions. The data processing at Remu Health Center Office in Sorong City has not been fully computerized, as for the procedure carried out is that the personnel section receives employee data files in form and is copied back into the personnel archive or blank form from Sorong City Health Office which will be sent back to Sorong City Health Office and continued keeping in a cupboard. This way can make searching for employee data more difficult if at any time the data is needed. The method used in the development and design of this system is the waterfall method with a descriptive approach. The waterfall method process, namely the work of a system is carried out sequentially. The conclusion of this research is that with the employee data information system, users are able to search data, add data and store data permanently as well as reporting for all stored data.